KGB operations against the USA and Canada in Soviet Ukraine, 1953-1991 - Zhuk, S. I. (Sergeĭ Ivanovich), author.
1 online resource.
Keywords: "Oriented for a general reading audience, this book gives a unique and rare perspective on the KGB "special operations," in Soviet Ukraine, which targeted especially the USA and Canada, using the issues related to Soviet Ukrainian identity and cultural diplomacy of Soviet Ukraine after Stalin's death in 1953 until the perestroika of the 1980s. Concentrating on the period of the Cold War after Stalin and combining the counterintelligence documents from of the KGB archive in Kyiv, Ukraine, with the official KGB correspondence and reports to the political leadership of Soviet Ukraine, this book offers the experimental view of political and cultural history of the relations between Soviet Ukraine and "capitalist America" through a prism of the KGB operations against the US and Canada. Written from a "hidden" perspective of the KGB operations from 1953 to the end of the 1980s, this book covers intelligence and counter-intelligence operations and the active measures of the KGB, but also various problems of anti-American cultural campaigns in Soviet Ukraine, sponsored by the KGB, involving the issues of cultural consumption, knowledge production, youth culture and national identity. Using carefully researched archive materials, this is an invaluable resource for scholars and advanced students of the KGB Operations, the Cold War, counterintelligence, and political and cultural history"--